EDUKASI KESEHATAN REPRODUKSI MELALUI MEDIA LEMBAR BALIK CATIN TERHADAP PENGETAHUAN DAN SIKAP CALON PENGANTIN DI PUSKESMAS KECAMATAN TANJUNG PRIOK - Shafa Adzkia Aulia, (2024)
The provision of reproductive health education before marriage needs to be given to prospective brides to prepare for marriage to build a healthy and prosperous family. The results of a survey of prospective brides at the Tanjung Priok Sub-District Health Center, only 22 out of 90 prospective brides (24%) had ever received reproductive health education. This study aims to see the difference in the level of knowledge and attitudes of prospective brides at the Tanjung Priok District Health Center before and after being given education through the Catin Flip Sheet media. This study used a pre-experimental design of one group pre-test and post-test which was conducted in December 2023-January 2024 with a sample of 90 brides using a simple random sampling technique. Data was collected using questionnaires and analyzed using the Wilcoxon Test. The results showed that there was an increase in the average value of knowledge variables (6.97) and attitude variables (7.68) before and after being given education. There is a significant difference between the knowledge and attitude of prospective brides before and after being given education on reproductive health through the Catin Flip Sheet media (p < 0.05).